Telemedicine User Satisfaction in D3 Medical Records and Health Information Study Program Students - Putri, Meuthia Berliana; Ikawati, Fita Rusdian; Rusdi, Achmad Jaelani (PROMOTOR, 2025)
Technological advancements, especially in the field of internet, have driven the development of digital health services such as telemedicine. This service allows users to consult with medical personnel online, thus providing easy access to health services, especially in geographical areas that are difficult to reach. This study aims to identify the level of satisfaction of students of D3 Medical Records and Health Information Study Program ITSK RS.DR. Soepraoen Malang towards the use of telemedicine applications. The method used is End User Computing Satisfaction (EUCS), which includes five indicators: content, accuracy, format, ease of use, and timeliness. This study uses a descriptive quantitative method with a survey approach to 45 respondents. The results of the analysis showed that the majority of respondents were very satisfied with the use of telemedicine applications, with an average satisfaction score of 4.19. The indicator with the highest score was ease of use (4.26), while the content indicator obtained the lowest score (4.12). These results indicate that although the telemedicine application is considered easy to use, there are still aspects of content that need to be improved. This research is expected to be a recommendation for application developers to improve the quality of telemedicine systems and services to increase user satisfaction.